2014
DOI: 10.1017/s0030605312001238
|View full text |Cite
|
Sign up to set email alerts
|

Effects of livestock on guanacoLama guanicoedensity, movements and habitat selection in a forest–grassland mosaic in Tierra del Fuego, Chile

Abstract: Locally abundant ungulates often come into conflict with human activities. After a population collapse that reached its nadir in the s, the guanaco Lama guanicoe population in Tierra del Fuego, Chile, recovered and is now in conflict with sheep ranching and commercial logging. We studied the effects of livestock density and environmental factors on guanaco abundance and spatial ecology, using seasonal counts and radio-telemetry in a private protected area (Karukinka) and neighbouring ranches in a forest-gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 47 publications
(64 reference statements)
1
25
0
Order By: Relevance
“…Lama guanicoe Guanaco ? (Moraga et al, 2015) Cervidae Alces alces Moose + (Sweanor and Sandegren, 1988;Andersen, 1991b) ? (Histol and Hjeljord, 1993;Singh et al, 2012) ?…”
Section: Connochaetes Taurinusmentioning
confidence: 99%
“…Lama guanicoe Guanaco ? (Moraga et al, 2015) Cervidae Alces alces Moose + (Sweanor and Sandegren, 1988;Andersen, 1991b) ? (Histol and Hjeljord, 1993;Singh et al, 2012) ?…”
Section: Connochaetes Taurinusmentioning
confidence: 99%
“…Approximately two-thirds of the population is migratory; other individuals are resident in the summer or winter range throughout the year [ 23 – 25 ]. Although La Payunia Reserve is one of the few sites in South America where long-distance ungulate migrations are well documented, shorter migrations and other seasonal movements of guanacos are known to occur in other areas and likely were more common in the past when guanaco populations were large and barriers to movement were less common [ 22 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The guanaco, as a generalist herbivore of intermediate selection, is capable of consuming most available species of plants, from grasses to ligneous species, but mainly bushes. 14,36,43,44 Indirect evidence suggests that prairies are the preferred habitat for guanacos in Tierra del Fuego, but that they use forest patches due to displacement by sheep. 3 In a continental site where the guanacos were sedentary, it was shown that the ewes excluded guanacos from the prairies through resource competition.…”
Section: Eaba Easjmentioning
confidence: 99%